2011
DOI: 10.1007/s11191-011-9370-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of the “Tree” Analogy in Evolution Teaching by Biology Teachers

Abstract: This work discusses the use of Darwin's 'Tree of Life' as a didactic analogy and metaphor in teaching evolution. It investigates whether biology teachers of pupils from 17 to 18 years old know Darwin's text 'Tree of Life'. In addition, it examines whether those teachers systematically employ either the analogies present in that text or other analogies between the tree and evolution, and whether they adopt a specific methodology for teaching with analogies and metaphors (A&M). The academic training of teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…A few studies indicate that teachers lack knowledge for teaching evolution (Marcelos and Nagem 2011;van Dijk 2009). The most neglected area of teacher preparation is PCK, as we found no examples in which PCK was an explicit goal for preparing teachers to teach evolution.…”
Section: Goal #5: Pedagogical Content Knowledgementioning
confidence: 99%
“…A few studies indicate that teachers lack knowledge for teaching evolution (Marcelos and Nagem 2011;van Dijk 2009). The most neglected area of teacher preparation is PCK, as we found no examples in which PCK was an explicit goal for preparing teachers to teach evolution.…”
Section: Goal #5: Pedagogical Content Knowledgementioning
confidence: 99%
“…On the other hand, it is observed that analogy studies are carried out less in biology than in other fields and that most studies are carried out in the field of chemistry. The fact that there are fewer abstract subjects in biology than in other fields would be the reason (Lawson, 2001;Marcelos & Nagem, 2012). Analogy studies conducted in the field of biology are among the subjects of "Cell and Structure" and "Systems in our body", where abstract concepts are most difficult for students, and analogy examples are more common in teaching (Digilli, 2014).…”
Section: Solar Systemmentioning
confidence: 99%
“…Elas levam a descobertas, sendo usadas para a explicação de teorias científicas transmitidas de geração a geração. Por tal característica também estimulam a interpretação da realidade (DUIT, 1991;FABIÃO;DUARTE, 2006;MARCELOS;NAGEM, 2009). Almeida (2020) aponta que a temática em Educação em Ciências possui demandas quando se olha para a formação de professores e o trabalho com as questões de linguagem.…”
Section: Fundamentação Teóricaunclassified